A feasible strategy to constructing hybrid conductive networks in PLA‐based composites modified by CNT‐d‐RGO particles and PEG for mechanical and electrical properties. (14th November 2019) - Jia, Shikui; Yu, Demei; Zhu, Yan; Su, Xiaolong; Wang, Zhong; Chen, Ligui
Abstract : Carbon nanotubes (CNTs) and reduced graphene oxide (RGO) were successfully assembled by chemical reaction to obtain CNT‐d‐RGO particles. Then, a home‐made dynamic impregnating device was used to prepare hybrid CNT‐d‐RGO/polyethylene glycol (PEG). Next, the different modifiers, including CNTs, GO, CNT‐d‐RGO, PEG, and CNT‐d‐RGO/PEG, were, respectively, added into poly‐(lactic acid) (PLA) matrix via melt‐compounding. The dispersed morphology for these different modifiers within the PLA matrix was confirmed by SEM and TEM observations. Especially, compared with the identical weight ratio of CNT‐d‐RGO, the hybrid CNT‐d‐RGO/PEG within the PLA matrix exhibited an excellent exfoliated and interconnected networks morphology. Moreover, compared with pure PLA, not only the crystallinity of all PLA‐based composites notably improved, but half‐crystallization time was also shortened. Furthermore, despite the addition of different modifiers, the crystal form of PLA‐based composites remained unchanged. Noticeably, compared with those of pure PLA, the tensile stress, strain, and modulus of PLA composite added with CNT‐d‐RGO/PEG increased by 29.4%, 4.1%, and 56.1%, respectively, and the V‐notch impact strength slightly improved. In addition, compared with pure PLA, volume resistivity of the PLA composite added with 1 wt% CNT‐d‐RGO/PEG decreased by 93.1%, and its volume conductivity increased by five orders of magnitude.